Developing implementation strategies for promoting integrative oncology outpatient service delivery and utilisation: a qualitative study in Hong Kong - Ho, Leonard; Kwong, Ming Hong; Li, Angus S. C.; Nilsen, Per; Ho, Fai Fai; Zhong, Claire C. W.; Wong, Charlene H. L.; Lin, Wai Ling; Chung, Vincent C. H. (Frontiers in Public Health, 2024)
Purpose Current evidence supports the use of integrative oncology (IO) interventions in cancer supportive care. The demand for outpatient IO services in Hong Kong is expected to soar following the surge in cancer incidence due to population ageing. This study identified the factors influencing the delivery and utilisation of outpatient IO from local stakeholders’ perspectives and developed corresponding implementation strategies. Methods This study involved two sequential stages. First, with individual semi-structured interviews guided by the Theoretical Domains Framework (TDF), we explored stakeholders’ views on the barriers to and facilitators for implementing IO. Second, guided by a TDF-based qualitative data analysis of interview transcripts, we performed intervention mapping to develop Behaviour Change Wheel-based implementation strategies that may overcome the barriers and strengthen the facilitators. Results We interviewed 31 stakeholders, including traditional Chinese medicine (TCM) practitioners (n = 8), biomedically-trained doctors (n = 7), nurses (n = 6), administrators (n = 4), caregivers (n = 4), and pharmacists (n = 2). The key local factors influencing outpatient IO are (1) lacking nursing and administrative workforce supporting IO service delivery, (2) lacking awareness of IO services among healthcare professionals, administrators, patients, and caregivers, and (3) lacking knowledge among healthcare professionals of herb–drug interaction and herbal toxicities. Conclusion We recommended a multi-faceted implementation strategies package that included arranging funding to train, recruit, and retain nursing and administrative staff, devolving resources into promoting interprofessional collaborations and evidence on IO effectiveness and safety, integrating evidence on herb–drug interactions and herbal toxicities into automated electronic health record systems monitored by pharmacists with dual qualifications in TCM and conventional pharmacy.